Analisis Dampak Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Kedai Tea House Masamba - Amar Amar; Anwar M Suhardi; Andi Rizkiyah Hasbi (Universitas Batanghari Jambi, 2023)
The purpose of this research is to test, analyze and explain the impact of digital marketing and service quality on purchasing decisions. This independent research variable is digital marketing and service quality. While the dependent variable in this study is the purchase decision. This type of research uses quantitative research methods. The sample for this study was determined based on a minimum sample size of 10 times the number of measurement items used in the study. The analytical method used is linear regression analysis. The results of this study indicate that digital marketing variables have no significant effect on purchasing decisions. The service quality variable has a positive and significant effect on purchasing decisions.